Prospective evaluation of a continuous infusion vancomycin dosing nomogram in critically ill patients undergoing continuous venovenous haemofiltration. (11th October 2017) - Sin, Jonathan H; Newman, Kelly; Elshaboury, Ramy H; Yeh, D Dante; de Moya, Marc A; Lin, Hsin
Abstract: Objectives: The most optimal method of attaining therapeutic vancomycin concentrations during continuous venovenous haemofiltration (CVVH) remains unclear. Studies have shown continuous infusion vancomycin (CIV) achieves target concentrations more rapidly and consistently when compared with intermittent infusion. Positive correlations between CVVH intensity and vancomycin clearance (CLvanc ) have been noted. This study is the first to evaluate a CIV regimen in patients undergoing CVVH that incorporates weight-based CVVH intensity (mL/kg/h) into the dosing nomogram. Methods: This was a prospective, observational study of patients undergoing CVVH and receiving CIV based on the nomogram. The primary outcome was achievement of a therapeutic vancomycin concentration (15–25 mg/L) at 24 h. Secondary outcomes included the achievement of therapeutic concentrations at 48 and 72 h. Results: The nomogram was analysed in 52 critically ill adults. Vancomycin concentrations were therapeutic in 43/52 patients (82.7%) at 24 h. Of the nine patients who were not therapeutic at 24 h, seven were supratherapeutic and two were subtherapeutic. The mean (SD) concentration was 20.1 (4.2) mg/L at 24 h, 20.7 (3.7) mg/L at 48 h and 21.9 (3.5) mg/L at 72 h. Patients with CVVH intensity >20 mL/kg/h experienced higher CLvanc at 24 h compared with patients with CVVH intensity <20 mL/kg/h (3.1 versus 2.6 L/h; P = 0.013). Conclusions: By incorporating CVVH intensity into the CIV dosing nomogram, the majority of patients achieved therapeutic concentrations at 24 h and maintained them within range at 48 and 72 h. Additional studies are required to validate this nomogram before widespread implementation may be considered.